Annual report 2017: CGIAR Excellence in Breeding Platform - CGIAR Excellence in Breeding Platform (CGIAR Excellence in Breeding Platform, 2018)
The platform leader was hired in August of 2017. The platform leader, Michael Quinn, and CIMMYT DDG, Marianne Bänziger, visited a large number of CGIAR-supported breeding programs – Africa Rice (Nigeria), CIAT (Colombia), CIMMYT (Kenya, India, Mexico), CIP (Kenya, Peru), ICRAF (Kenya), ICRISAT (Kenya, India), IITA (Nigeria), ILRI (Kenya), BeCA (Kenya), IRRI (Philippines, India), WorldFish (Malaysia) – to better understand challenges, needs and opportunities, and to explain how EiB can provide value to CGIAR breeding institutions and how best to work with EiB. A membership agreement that describes the commitments expected of breeding programs participating in EiB and the benefits they can expect to receive in turn was developed and distributed to CGIAR institutions. Signed membership agreements were returned from most CGIAR breeding programs.